Reducing catheter-associated urinary tract infections in the cardiac intensive care unit with a coordinated strategy and nursing staff empowerment - Poonam Gupta; Mincy Thomas; Leena Mathews; Cherlyn Simbulan; Ma Leni Garcia; Mawahib El Hassan; Nidhu Zacharia; Ashraf Fayiz Ibrahim; Fatma Attia Mohamed (BMJ Open Quality)
Background Catheter-associated urinary tract infection (CAUTI) is one of the most common hospital-acquired infections. The use of urinary catheters is associated with several complications and increased mortality and morbidity. At the coronary intensive care unit (CICU) of a tertiary cardiac care facility, the CAUTI rate was 7.6/1000 catheter days in January 2017. In collaboration with the Institute for Healthcare Improvement, we implemented evidence-based practices in the form of bundles based on the value improvement methodology to eliminate CAUTIs in the CICU.Methods This initiative aimed to reduce the CAUTI rate using a multifaceted approach. The key interventions were empowering front-line nurses for automatic stop orders and ensuring compliance to the catheter insertion and maintenance bundles. We used a model for improvement and tested the changes using small plan–do–study–act cycles. Surveillance methods and CAUTI definitions proposed by the National Healthcare Safety Network were used to monitor the outcomes. Monthly rates of CAUTIs 24 months before the intervention were compared with those 44 months after the intervention using an independent t-test. Statistical significance was set at p<0.05.Results The rate of CAUTIs dropped from 7.6 per 1000 catheter days in January 2017 to 0 from October 2021 to August 2022. The unit had achieved 280 calendar days free of CAUTI untill August 2022.Conclusions Behavioural changes, including empowerment of nurses and adherence to all elements of the care bundle, led to significant and sustained improvement in reducing the CAUTI rate in the adult CICU.